Immigration and the constraints of justice between open borders and absolute sovereignty - Pevnick, Ryan, 1980-; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
"This book explores the constraints which justice imposes on immigration policy. Like liberal nationalists, Ryan Pevnick argues that citizens have special claims to the institutions of their states. However, the source of these special claims is located in the citizenry's ownership of state institutions rather than in a shared national identity. Citizens contribute to the construction and maintenance of institutions (by paying taxes and obeying the law), and as a result they have special claims to these institutions and a limited right to exclude outsiders. Pevnick shows that the resulting view justifies a set of policies - including support for certain types of guest worker programs - which is distinct from those supported by either liberal nationalists or advocates of open borders. His book provides a framework for considering a number of connected topics including issues related to self-determination, the scope of distributive justice and the significance of shared national identity"--
Machine generated contents note: 1. Introduction; 2. Statism, self-determination and associate ownership; 3. Refining associative ownership; 4. Rights-based arguments for open borders; 5. Distributive justice and open borders; 6. The significance of national identity; 7. Applications; 8. Works cited.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Emigration and immigration -- Government policy; Distributive justice; Electronic books